Analisis Penerapan Akuntansi Pertanggungjawaban Anggaran Sebagai Bentuk Pengendalian Biaya Pada Dinas Perhubungan Kota Prabumulih - Rosalia Septiasari; Meirani Betriana; Emi Sukmawati (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to determine the implementation of budget accountability accounting as a form of cost control at the Prabumulih City Transportation Agency. The type of research used in this study is qualitative research. Data collection techniques in this study were carried out through observation, interviews, documentation, and literature studies. The data obtained from this study were in the form of primary and secondary data. The results of this study indicate that the Prabumulih City Transportation Agency has implemented most of the five main requirements/elements of accountability in accounting, which is supported by a clear organizational structure in accordance with Mayoral Regulation Number 41 of 2025. Budget preparation is carried out in a participatory manner. The classification of account codes is integrated with the SIPD system based on Permendagri Number 90 of 2019. As well as accountability reports that are implemented optimally through the digitalization of the SIPD system in the form of LRA.